ANALISISPERBEDAAN FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PROFITABILITAS BANK KONVENSIONAL DAN BANK SYARIAH DI INDONESIA PERIODE TAHUN 2011 - 2018 - Priono, Andri; Pangestuti, Irene Rini Demi (Faculty of Economics and Business Diponegoro University, 2019)
This study aims to analyze how profitability differs between conventional banks and Islamic banks in Indonesia by analyzing the effect of Equity to Total Assets (ETA), Loan Loss Provision (LLP), Loan to Total Assets (LTA), Operation Costs (OC), Size , Non Interest Income (NII), and Market Power (MP) to ROA.Currently, Islamic banks are developing rapidly in Indonesia. Many conventional banks began to open sharia activities, so that the majority of Indonesian people who are Muslim can use the services of banks without having to fear usury (riba). The sample in this study is conventional commercial banks that open business activities according to sharia principles, and all Islamic commercial banks which are subsidiaries of conventional commercial banks or the results of conversion from conventional commercial banks, with the period from 2011 to 2018 and their financial statements can be accessed through Otoritas Jasa Keuangan (OJK) website, Bloomberg, and official website of the these banks. The method used in this study uses multiple regression analysis with a hypothesis testing tool that is the t test and the F test. However, before conducting multiple regression analysis, the classical assumption test is first performed. To analyze the differences, the Chow-Test and Independent-T Test Sample are used.Through partial hypothesis test results (t test) on conventional commercial banks, it shows that LLP, LTA, SIZE, NII, and MP variables have a significant effect on ROA. Whereas Islamic banks show that the variables ETA, LLP, OC, NII, and MP significantly influence ROA. Adjusted RÂ² in regression models with conventional banks amounted to 80.1%; whereas in Islamic banks is 76.6%. Based on the Chow-Test it can be concluded that there are significant differences from the influence of independent variables on ROA of conventional commercial banks and Islamic commercial banks so that the profitability between the two types of banks is different.